2009
DOI: 10.1111/j.1365-2702.2008.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis patient education: RA patients’ experience

Abstract: The results provide a useful insight into RA patient education. Nurses should avoid merely passing on information in a routine workmanlike way. It is important that they take time to discuss their patients' feelings and worries especially with newly diagnosed patients. RA patient education should balance patients' information needs with their need for emotional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 28 publications
0
51
0
3
Order By: Relevance
“…Most described various feelings such as loneliness, depression and anxiety. Some research has shown that positive interaction which enabled chronically ill adults to ask questions and receive emotional support increased their self-confidence and feelings of security [12,21] . However, for most of the disease groups counseling was imposed on chronically ill adults rather than being agreed with them, and was not always carried out in a positive atmosphere for discussing emotions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most described various feelings such as loneliness, depression and anxiety. Some research has shown that positive interaction which enabled chronically ill adults to ask questions and receive emotional support increased their self-confidence and feelings of security [12,21] . However, for most of the disease groups counseling was imposed on chronically ill adults rather than being agreed with them, and was not always carried out in a positive atmosphere for discussing emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals' level of knowledge about their disease varies, and they may have different expectations about the content of the counseling [20,24,25] . In addition, there is currently a lack of planning in patient counseling, which does not always take account of individual needs [12,14,26,27] . Although individual counseling is known to have positive effects on self-management and compliance [17,[28][29][30] , positive outcomes are not inevitable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with rheumatoid arthritis (RA) were found to have a moderate knowledge of how to use anti-rheumatic drugs and NSAIDs (Mäkeläinen et al, 2009a) and about half of the patients (n = 173) were satisfi ed with patient education given by rheumatology nurses. The patients who were dissatisfi ed felt that the rheumatology nurses had not tailored the information to their needs (Mäkeläinen et al, 2009b). Nearly a third of the patients with RA (n = 86) who received therapy with anti-rheumatic drugs, corticosteroids and NSAIDs were consistently compliant.…”
Section: Introductionmentioning
confidence: 99%
“…Research evidence shows that patient outcomes may be improved through individual nursing interventions [7]. Previous studies find that patients with arthritis are mostly preferred to individual nurse-delivered education by one-to-one communication on certain themes [8] [9]. While existing studies [10]- [12] investigate the effects of nursing education on the management of psoriasis, these studies do not focus on the specific type of psoriasis, psoriatic arthritis, and may be failed to include the educational component of how to manage symptoms of arthritis.…”
mentioning
confidence: 99%